Association of Hepatitis C Virus (HCV) Infection and Human Leukocyte Antigens (HLA) - Hasan , Abdul-Razak SH; Al-Ajeeli, Karim Sadun Ali (Diyala Journal of Medicine, 2019)
Back ground: Several previous reports on the association between hepatitis C virus (HCV) infection and certain human leukocyte antigens (HLA) have yielded controversial results. Objectives: This study was conducted to explore the association of HCV infection and certain HLA in patients from Al-Ramadi Province. Subjects and methods: Thirty two patients with chronic HCV infection as well as 64 apparently healthy individuals and 30 patients with clinically evident acute viral hepatitis, but HCV negative were enrolled in the present study which was conducted in Al-Ramadi city for the period from August/2004 to May/2006. HCV infection was diagnosed by detecting the anti-HCV antibody by enzyme-linked immunosorbant assay (ELISA) and confirmed by Immunoblot assay. Determination of HLAs was done by Microlymphocytotoxicity technique. Results: The results revealed that the presence of HLA-DR5 (Odd ratio 2.7, P 0.022) and HLA-DQ2 (Odd ratio 3.1, P= 0.008), and the absence of HLA-DR7 (Inverse Odd ratio 3.2, P = 0.04) and HLA-DQ1 (Inverse Odd ratio 2.8, P= 0.012) were associated with significantly increased risk for HCV infection as compared to healthy controls. On the other hand, the presence of HLA-DR5 (Odd ratio 6.5, P= 0.005) and HLA-DQ2 (Odd ratio 5.1, P= 0.002), and the absence of HLA-DR7 (Inverse Odd ratio 4.8, P= 0.018) were significantly associated with increased risk for HCV infection. Conclusion: Genetic predisposition may play a role in hepatitis C virus infection in patients from Al-Ramadi city.